RELATIONSHIP BETWEEN LOCATION AND NUMBER OF LESIONS BASED ON HEAD CT SCAN WITH BEHAVIORAL PSYCHOLOGICAL SYMPTOMS OF DEMENTIA: A Study on Post-Ischemic Stroke Patients with Vascular Cognitive Impairment at Kariadi Hospital Semarang - Novalya, Fadhilla Eka; Puspita Wati, Arinta; Kustiowati, Endang; Tugasworo, Dodik; Muhartomo, Hexanto (RSUP Dr. Kariadi, 2026)
Background: Behavioral Psychological Symptoms of Dementia (BPSD) characterized by disturbances in perception, thought content, mood, or behavior, frequently occur alongside Vascular Cognitive Impairment (VCI), significantly affecting the functional and cognitive status of post-stroke patients. Previous studies have identified certain stroke characteristics — such as multiple lesions, infarct volume and lesion location (e.g. left hemisphere) — as risk factors for post-stroke dementia. Epidemiological data on BPSD and research on the relationship between the location and number of stroke lesions and BPSD remain limited. Aim: To determine the relationship between the location and number of stroke lesions based on head CT scan with BPSD Methods: Cross-sectional study involving post-ischemic stroke patients at the Outpatient Installation of Kariadi Hospital Semarang. An evaluation was conducted on the location and number of stroke lesions in relation to the occurrence of Behavioral Psychological Symptoms of Dementia, based on Abe’s Behavioral Psychological Symptoms of Dementia Score. The confounding variables of the study were age, occupation, education level, nutritional status, and caregiver. Analysis was conducted using the Independent T test, Mann Whitney U and Kruskal-wallis. Significant results p<0.05 Results: The mean ABE BPSD score was 7.17 with a median of 4. The most common symptoms were depression/low mood, irritability, and sleep disturbance (33.3% each), followed by excitement and agitation (28.6%). Of the total subjects, 31% had stroke in the non-dominant hemisphere, 26.2% in the dominant hemisphere, and 42.9% in both hemisphere. A total of 64.3% had frontal lesions, while 35.7% had non-frontal lesions. Based on the number of lesions, 54.8% had single lesions and 45.2% had multiple lesions. The location of the lesions in the frontal region (p<0.001), the number of multiple lesions (p<0.001) and younger age (p=0.042) were significantly associated with a more severe ABE BPSD score. Conclusion: Location of frontal lesions, number of multiple lesions based on head CT scan and younger age have significant association with BPSD in post-ischemic stroke patients with VCI.